(untitled) (Italian Journal of Public Health, 2010)
Background: Evidence should drive public health initiatives to better address the most important health issues. Chronic diseases represent the main burden of healthcare expenditure in Western countries and are determined by risk factors related to behaviour. Population-based surveys should lead to well informed decision making in this field. Methods: A cross-sectional survey was carried out among the general population aged between 18 and 69 in the district of Monza-Brianza in Northern Italy through phone interviews. A validated questionnaire investigating health-related lifestyles and behaviours was used. The questionnaire was divided into the following parts: general health status, physical activity, smoking habit, nutrition, alcohol consumption, driving safety, cardiovascular risk, cancer screening, mental health, domestic safety and socio-economic status. Results: In total, 308 interviews were carried out (response rate=76%). Almost 40% reported a body mass index >25, 64.9% had high school or university degrees, 60.4% worked full-time, 26.2% were assessed as physically inactive, and 13.3% were on a weight –loss diet. In addition, 19.7% had an “at risk” alcohol consumption , especially among younger age groups. Symptoms of depression were identified in 4.9% of the study subjects, particularly in women. Conclusions: Age, body mass index, education, and occupation were significantly associated with the likelihood of reporting poor health status. Young subjects were more likely to be smokers and drinkers at risk. Psychological health and appropriate prescription of anti-cholesterol and anti-hypertensive drugs are areas deserving further investigations. Nutrition, physical activity, driving safety and youth health, especially concerning drinking habits, are areas where initiatives should be undertaken